Prosedur Pemeriksaan CT-Scan Angiography (CTA) Upper Ekstremity Pada Kasus Pseudoaneurisma Arteri Subclavia Kanan Di Rumah Sakit Primaya Tangerang - Muhammad Faisal; I Putu Eka Juliantara; Edwien Setiwan Saputra (JURNAL RISET RUMPUN ILMU KESEHATAN, 2023)
Upper Extremity CT-Scan Angiography (CTA) Examination Procedure in Right Subclavian Artery Pseudoaneurysm Cases at Primaya Hospital Tangerang. Upper Extremity CT-Scan Angiography (CTA) is described as a technique for non-invasively evaluating vascular structures via peripheral contrast injection. Upper Extremity CTA is carried out starting from patient preparation, tools and materials used, examination protocols, and image reconstruction techniques. In addition, the contrast infusion technique must also be appropriate to provide an informative image. The purpose of this study was to determine the procedure for examining the Upper Extremity CTA in cases of subclavian artery pseudoaneurysm with excess of the Upper Extremity CTA. This research is a qualitative research with a case study method using 1 patient. Data were collected using observation, documentation and radiographer interview methods. The results of the data collected can be concluded with the Upper Extremity CTA procedure using Scanning Scannogram, pre-contrast, & post-contrast arterial phase, and venous phase, then image reconstruction from the MPR image and 3D VR image. The advantages of the CTA procedure using the smart prep technique image resolution quality could be higher.